Effect of Aerobic Exercise Training and Essential Amino Acid Supplementation for 24 Weeks on Physical Function, Body Composition, and Muscle Metabolism in Healthy, Independent Older Adults: A Randomized Clinical Trial - Markofski, Melissa M; Jennings, Kristofer; Timmerman, Kyle L; Dickinson, Jared M; Fry, Christopher S; Borack, Michael S; Reidy, Paul T; Deer, Rachel R; Randolph, Amanda; Rasmussen, Blake B; Volpi, Elena (The journals of gerontology. Series A, Biological sciences and medical sciences, 2019)
Essential amino acids (EAA) and aerobic exercise (AE) acutely and independently stimulate skeletal muscle protein anabolism in older adults. In this Phase 1, double-blind, placebo-controlled, randomized clinical trial, we determined if chronic EAA supplementation, AE training, or a combination of the two interventions could improve muscle mass and function by stimulating muscle protein synthesis. We phone-screened 971, enrolled 109, and randomized 50 independent, low-active, nonfrail, and nondiabetic older adults (age 72 ± 1 years). We used a 2 × 2 factorial design. The interventions were: daily nutritional supplementation (15 g EAA or placebo) and physical activity (supervised AE training 3 days/week or monitored habitual activity) for 24 weeks. Muscle strength, physical function, body composition, and muscle protein synthesis were measured before and after the 24-week intervention. Forty-five subjects completed the 24-week intervention. VO2peak and walking speed increased (p < .05) in both AE groups, irrespective of supplementation type, but muscle strength increased only in the EAA + AE group (p < .05). EAA supplementation acutely increased (p < .05) muscle protein synthesis from basal both before and after the intervention, with a larger increase in the EAA + AE group after the intervention. Total and regional lean body mass did not change significantly with any intervention. In nonfrail, independent, healthy older adults AE training increased walking speed and aerobic fitness, and, when combined with EAA supplementation, it also increased muscle strength and EAA-stimulated muscle protein synthesis. These increases occurred without improvements in muscle mass.